Negative pole piece and preparation method thereof, lithium ion battery and electric equipment

By designing scientifically graded negative electrode sheets in lithium-ion batteries, using the first and second active silicon materials and activated carbon materials, combined with conductive agents, the compaction density and stability of silicon materials are solved, and the battery is improved Dynamics and cycling performance enable high energy density battery design.

CN119230744APending Publication Date: 2024-12-31ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411519691.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The rigidity and low compaction density of silicon materials in lithium-ion batteries lead to easy crushing in actual use, resulting in side reactions between the internal active silicon materials and the electrolyte, accelerated battery capacity decline and increased battery cell expansion, which is difficult for the existing technology. Effectively improve the compaction density and stability of silicon materials.

Method used

The design of the negative electrode sheet is adopted, including the negative electrode current collector and the negative electrode active material layer arranged on one side. The negative electrode active material layer consists of the first and second active silicon materials and activated carbon materials, and the particle size and content are scientifically graded. , combined with conductive agent, binder and thickener, to form high strength and high compaction density pole sheets.

Benefits of technology

It effectively improves the dynamic performance and long cycle performance of lithium-ion batteries, improves energy density, and has a simple process and low cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230744A_ABST
    Figure CN119230744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a negative pole piece and a preparation method thereof, a lithium ion battery and electric equipment. The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, and the negative electrode active material layer comprises an active silicon material and an active carbon material; the active silicon material comprises a first active silicon material and a second active silicon material, the Dv50 particle size of the first active silicon material is 1-5 [mu] m, and the Dv50 particle size of the second active silicon material is 7-10 [mu] m. The negative pole piece provided by the invention has high strength and high compaction density, can effectively improve the dynamic performance and long cycle performance of the lithium ion battery, and is relatively high in energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode plate and a preparation method thereof, a lithium ion battery and an electrical device. Background Art

[0002] After more than 30 years of development since its commercialization, lithium-ion batteries are now widely used in various fields. In the field of electronic consumer products, mobile phones, laptops, Bluetooth headsets, and various smart wearable devices have an increasing demand for lithium-ion batteries. In addition, as countries pay more and more attention to environmental pollution issues, the demand for clean energy in various countries is becoming more and more intense, and the demand for lithium-ion batteries in clean energy storage, electric vehicles, power tools and other fields is also increasing. With the rapid development of science and technology, the demand for lithium-ion batteries is not only reflected in quantity, but also puts higher requirements on the performance of lithium-ion batteries. Continuously improving the energy density of lithium-ion batteries and developing high-energy-density lithium-ion batteries have become an inevitable trend in the development of lithium-ion batteries.

[0003] In terms of improving energy density, increasing the theoretical specific capacity of the negative electrode active material of lithium-ion batteries is one of the most effective ways. The theoretical specific capacity of silicon materials at room temperature is as high as 3579mAh / g, which is more than 10 times the theoretical specific capacity of graphite negative electrodes in commercial lithium-ion batteries today. In the short term, it is considered to be the most promising negative electrode material to be commercially applied to improve the energy density of lithium-ion batteries. However, due to its high rigidity and lower compaction density than graphite, silicon materials are easily crushed during actual use, resulting in direct exposure of the internal active silicon materials to the electrolyte and side reactions, accelerated battery capacity decay and increased cell expansion. Therefore, how to improve the actual use compaction density window of silicon materials and improve the stability of the pole piece is an urgent problem to be solved in the application of silicon materials in lithium-ion battery negative electrodes.

[0004] In the prior art, in order to improve the compaction density of silicon materials, the following solutions are available: 1. Using surface-coated graphene and other materials with slip function to improve the compaction density of silicon materials, but the graphene and other coating materials introduced by this method will accelerate the side reaction with the electrolyte, resulting in the degradation of electrical performance; 2. Improving the compaction density of materials by increasing the particle size of silicon materials, but simply increasing the particle size will cause the diffusion path of lithium ions in the silicon material to be lengthened, resulting in the deterioration of kinetic performance; 3. Improving the compaction density of the overall negative electrode sheet by matching softer high-compacted graphite, but high-compacted graphite usually leads to the degradation of kinetic performance and increased costs. Therefore, the present invention proposes a new solution. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a negative electrode plate and a preparation method thereof, a lithium ion battery and an electrical device.

[0006] In a first aspect, the present invention provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the components of the negative electrode active material layer include active silicon material and active carbon material;

[0007] The active silicon material comprises a first active silicon material and a second active silicon material. The Dv50 particle size of the first active silicon material is 1-5 μm, and the Dv50 particle size of the second active silicon material is 7-10 μm.

[0008] As a preferred technical solution of the present invention, based on the total mass of the active silicon material being 100%, the mass content of the first active silicon material is 15-40%.

[0009] As a preferred technical solution of the present invention, based on the total mass of the active silicon material and the active carbon material being 100%, the content of the active silicon material is 2-30%.

[0010] As a preferred technical solution of the present invention, based on the total mass of the active silicon material and the active carbon material being 100%, the content of the active silicon material is 5-20%.

[0011] As a preferred technical solution of the present invention, the particle breakage ratio of the active silicon material on the surface of the negative electrode plate is ≤5%.

[0012] As a preferred technical solution of the present invention, the particle breakage ratio of the active silicon material on the surface of the negative electrode plate is ≤2%.

[0013] As a preferred technical solution of the present invention, the first active silicon material and the second active silicon material each independently include SiO x , any one or more of pre-lithiated silicon oxide, pre-magnesium silicon oxide, silicon alloy, sand-ground silicon carbon and vapor deposited silicon carbon, wherein 0<x<2.

[0014] As a preferred technical solution of the present invention, the first active silicon material and the second active silicon material are both selected from vapor deposited silicon carbon.

[0015] As a preferred technical solution of the present invention, the activated carbon material includes any one or more of artificial graphite, natural graphite, soft carbon, hard carbon and mesophase carbon microbeads.

[0016] As a preferred technical solution of the present invention, the compaction density PD1 of the first active silicon material is 0.95 g / cc≤PD1≤1.05 g / cc.

[0017] As a preferred technical solution of the present invention, the compaction density PD2 of the second active silicon material is 1.05 g / cc<PD2≤1.20 g / cc.

[0018] As a preferred technical solution of the present invention, the compaction density of the active silicon material is PD>PD2.

[0019] As a preferred technical solution of the present invention, the components of the negative electrode active material layer also include a conductive agent, a binder and a thickener.

[0020] As a preferred technical solution of the present invention, the conductive agent includes any one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene and conductive graphite, preferably carbon nanotubes.

[0021] As a preferred technical solution of the present invention, the binder includes any one or more of polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyaniline, polyimide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin and polyurethane resin, preferably polyacrylic acid salt, such as PAA-Na or PAA-Li.

[0022] As a preferred technical solution of the present invention, the thickener includes any one or more of CMC and its salts, preferably CMC-Na and / or CMC-Li.

[0023] As a preferred technical solution of the present invention, the mass content of the conductive agent in the negative electrode active material layer is 0.05-3%.

[0024] As a preferred technical solution of the present invention, the mass content of the binder in the negative electrode active material layer is 1-4%.

[0025] As a preferred technical solution of the present invention, the mass content of the thickener in the negative electrode active material layer is 0.1-1.6%.

[0026] In a second aspect, the present invention provides a method for preparing the negative electrode sheet described in the first aspect, the preparation method comprising: mixing active silicon material and active carbon material to obtain negative electrode active slurry, coating the negative electrode active slurry on the negative electrode collector to obtain the negative electrode sheet.

[0027] As a preferred technical solution of the present invention, the preparation method includes: mixing active silicon material, activated carbon material, conductive agent, binder, thickener and water to obtain negative electrode active slurry, coating the negative electrode active slurry on the negative electrode collector to obtain the negative electrode plate.

[0028] As a preferred technical solution of the present invention, the solid content of the negative electrode active slurry is 45-55%.

[0029] As a preferred technical solution of the present invention, the viscosity of the negative electrode active slurry is 3000-8000 Pa·S.

[0030] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the first aspect or the negative electrode sheet prepared by the preparation method described in the second aspect.

[0031] In a fourth aspect, the present invention provides an electrical device, wherein the electrical device comprises the lithium-ion battery described in the third aspect.

[0032] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0033] (1) The negative electrode plate provided by the present invention has high strength and high compaction density by scientifically grading the particle size and content of the active silicon material in the negative electrode active material layer, thereby effectively improving the kinetic performance and long cycle performance of the lithium-ion battery, and has a high energy density.

[0034] (2) The preparation method of the negative electrode plate provided by the present invention has simple process, low cost, is conducive to industrial production, and has broad prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0037] Figure 1 This is a schematic diagram of the structure of the negative electrode sheet described in Example 1 of the present invention;

[0038] Among them, 1-negative electrode current collector, 2-negative electrode active material layer, 3-first active silicon material, 4-second active silicon material, 5-activated carbon material.

[0039] Figure 2 A schematic diagram of particle crushing of active silicon material on the surface of the negative electrode plate according to Example 1 of the present invention;

[0040] Among them, 6-crushed silicon material particles. DETAILED DESCRIPTION

[0041] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0044] The theoretical specific capacity of silicon materials at room temperature is as high as 3579mAh / g, which is more than 10 times the theoretical specific capacity of graphite negative electrodes in commercial lithium-ion batteries today. In the short term, it is considered to be the most promising negative electrode material for commercial application to improve the energy density of lithium-ion batteries. However, due to its high rigidity and lower compaction density than graphite, silicon materials are easily crushed during actual use, resulting in direct exposure of the internal active silicon materials to the electrolyte and side reactions, accelerated battery capacity decay and increased cell expansion. Therefore, how to improve the actual use compaction density window of silicon materials and improve the stability of the pole piece is an urgent problem to be solved in the application of silicon materials in lithium-ion battery negative electrodes.

[0045] First, an embodiment of the present invention provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the components of the negative electrode active material layer include active silicon material and active carbon material;

[0046] The active silicon material includes a first active silicon material and a second active silicon material. The Dv50 particle size of the first active silicon material is 1-5 μm, and the Dv50 particle size of the second active silicon material is 7-10 μm. The schematic diagram of the structure of the negative electrode plate is as follows: Figure 1 shown.

[0047] The 1-5 μm may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc. The 7-10 μm may be 7 μm, 8 μm, 9 μm, 10 μm, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0048] The negative electrode sheet provided in the embodiment of the present invention has high strength and high compaction density, can effectively improve the dynamic performance and long cycle performance of lithium-ion batteries, and has high energy density. Specifically:

[0049] In the negative electrode plate provided by the embodiment of the present invention, the particle size of the first active silicon material is relatively small, and it can be effectively filled in the pores of the second active silicon material and the pores of the activated carbon material, thereby improving the compaction density of the plate, and because the particle size of the first active silicon material is relatively small, the diffusion path of lithium ions inside the silicon material particles is shortened, thereby improving the kinetic performance of the material; on the other hand, the particle size of the second active silicon pole material is relatively large, and it has a higher compaction density, which is beneficial to improving the overall compaction density of the negative electrode plate, thereby improving the cycle performance and energy density of the lithium-ion battery.

[0050] The embodiment of the present invention makes a differentiated design for the particle size of the first active silicon material and the second active silicon material, which effectively improves the compaction density and dynamic performance of the negative electrode plate; if the particle size of the first active silicon material is too small, the compaction density is low, and the particle grading effect is poor. The compaction density of the active silicon material powder after grading is lower than that of the second active silicon material, resulting in a decrease in the compaction density of the electrode plate, which in turn leads to a decrease in energy density, and the specific surface area of ​​the first active silicon material increases, and the side reaction of the electrolyte is aggravated, resulting in deterioration of the rate performance, cycle performance and expansion performance; if the particle size of the first active silicon material is too large, the first active silicon material and the second active silicon material cannot form an effective particle grading, and the compaction density of the active silicon material is reduced instead, and the increase in particle size leads to material dynamic loss, and even slight lithium precipitation may occur. Correspondingly, if the particle size of the second active silicon material is too small, the first active silicon material and the second active silicon material cannot form an effective particle grading. If the particle size of the second active silicon material is too large, the transmission path of lithium ions inside the particles will increase, resulting in a decrease in fast charging performance.

[0051] In some embodiments of the present invention, based on the total mass of the active silicon material being 100%, the mass content of the first active silicon material is 15-40%, for example, 15%, 20%, 25%, 30%, 35%, 40%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0052] When the mass content of the first active silicon material is within this range, the first active silicon material can be more fully filled in the pores of the second active silicon material and the activated carbon material, and the compaction density of the negative electrode sheet can be more effectively improved. Moreover, this content range can achieve the fast charging performance of the overall silicon-containing negative electrode sheet, while avoiding the degradation of the cycle performance and expansion performance caused by the increased side reaction with the electrolyte due to the excessive content of the first active silicon material with small particle size.

[0053] In some embodiments of the present invention, based on the total mass of the active silicon material and the active carbon material as 100%, the content of the active silicon material is 2-30%, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0054] When the content of active silicon material is within this range, the energy density of the battery can be more effectively improved, and the cycle performance and expansion performance are within an acceptable range. If the content of active silicon material is too low, the energy density of the battery may be reduced. If the content of active silicon material is too high, the dynamic performance, cycle performance and expansion performance of the battery may be reduced.

[0055] In some embodiments of the present invention, the content of the active silicon material is 5-20%, based on the total mass of the active silicon material and the active carbon material being 100%. When the content of the active silicon material is within this range, the battery's kinetic performance, cycle performance, expansion performance and other properties can be more effectively improved.

[0056] In some embodiments of the present invention, the particle crushing ratio of the active silicon material on the surface of the negative electrode plate is ≤5%, that is, when the negative electrode plate provided by the present invention is prepared, the crushing ratio of the active silicon material on the surface of the plate after rolling is obtained. The present invention counts the number of silicon particles on the surface of the negative electrode plate and the number of broken silicon particles. The particle crushing ratio of the silicon material = the number of broken silicon particles / the number of silicon particles can better judge the structural design strength of the silicon material and the structural stability of the negative electrode plate, thereby improving the energy density, cycle performance and expansion performance of the battery. The schematic diagram of the particle crushing of the active silicon material on the surface of the negative electrode plate of the present invention is as follows Figure 2 shown.

[0057] In some embodiments of the present invention, the particle breakage ratio of the active silicon material on the surface of the negative electrode plate is ≤2%. In this case, the negative electrode plate is more stable, so that the prepared lithium-ion battery has better dynamic performance and long cycle performance.

[0058] In some embodiments of the present invention, the first active silicon material and the second active silicon material each independently include SiO x , any one or more of pre-lithiated silicon oxide, pre-magnesium silicon oxide, silicon alloy, sand-ground silicon carbon and vapor deposited silicon carbon, wherein 0<x<2.

[0059] In some embodiments of the present invention, the first active silicon material and the second active silicon material are both selected from vapor deposited silicon carbon.

[0060] An embodiment of the present invention provides a method for preparing the vapor deposited silicon carbon, comprising: using a porous carbon matrix as a base material, introducing a silicon source for vapor deposition, depositing nano-silicon particles in the through holes of the porous carbon matrix, and finally carbon coating the vapor deposition product.

[0061] In some embodiments of the present invention, the activated carbon material includes any one or more of artificial graphite, natural graphite, soft carbon, hard carbon and mesophase carbon microbeads.

[0062] In some embodiments of the present invention, the compacted density PD1 of the first active silicon material is 0.95 g / cc≤PD1≤1.05 g / cc, such as 0.95 g / cc, 0.98 g / cc, 1.00 g / cc, 1.02 g / cc, 1.05 g / cc, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0063] In some embodiments of the present invention, the compaction density PD2 of the second active silicon material is 1.05 g / cc<PD2≤1.20 g / cc, such as 1.06 g / cc, 1.10 g / cc, 1.15 g / cc, 1.20 g / cc, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0064] In some embodiments of the present invention, the compaction density of the active silicon material is PD>PD2.

[0065] When the compaction density of the first active silicon material, the second active silicon material, and the active silicon material is within the above range, the compaction density of the negative electrode plate can be more effectively improved, thereby effectively improving the dynamic performance and long cycle performance of the battery.

[0066] In some embodiments of the present invention, the negative electrode active material layer further comprises a conductive agent, a binder and a thickener.

[0067] In some embodiments of the present invention, the conductive agent includes any one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene and conductive graphite, preferably carbon nanotubes.

[0068] In some embodiments of the present invention, the binder includes any one or more of polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyaniline, polyimide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin and polyurethane resin, preferably polyacrylic acid salt, such as PAA-Na or PAA-Li.

[0069] In some embodiments of the present invention, the thickener includes any one or more of CMC and its salts, preferably CMC-Na and / or CMC-Li.

[0070] In some embodiments of the present invention, the mass content of the conductive agent in the negative electrode active material layer is 0.05-3%, such as 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0071] In some embodiments of the present invention, the binder has a mass content of 1-4% in the negative electrode active material layer, such as 1%, 2%, 3%, 4%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0072] In some embodiments of the present invention, the mass content of the thickener in the negative electrode active material layer is 0.1-1.6%, such as 0.1%, 0.5%, 1%, 1.5%, 1.6%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0073] Accordingly, an embodiment of the present invention provides a method for preparing the negative electrode sheet, the method comprising: mixing active silicon material and active carbon material to obtain negative electrode active slurry, coating the negative electrode active slurry on a negative electrode current collector to obtain the negative electrode sheet.

[0074] In some embodiments of the present invention, the preparation method comprises: mixing active silicon material, activated carbon material, conductive agent, binder, thickener and water to obtain negative electrode active slurry, coating the negative electrode active slurry on the negative electrode collector to obtain the negative electrode plate.

[0075] In some embodiments of the present invention, the solid content of the negative electrode active slurry is 45-55%, such as 45%, 50%, 55%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0076] In some embodiments of the present invention, the viscosity of the negative electrode active slurry is 3000-8000 Pa·S, such as 3000 Pa·S, 4000 Pa·S, 5000 Pa·S, 6000 Pa·S, 7000 Pa·S, 8000 Pa·S, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0077] Accordingly, an embodiment of the present invention provides a lithium-ion battery, which includes the negative electrode sheet or the negative electrode sheet prepared by the preparation method.

[0078] Accordingly, an embodiment of the present invention provides an electrical device, wherein the electrical device includes the lithium-ion battery.

[0079] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its applications. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0080] If no specific techniques or conditions are specified in the examples, the conventional techniques or conditions in the art, or the techniques or conditions described in the literature, or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0081] The following embodiments involve the compaction density of the first active silicon material, the second active silicon material or the active silicon material, and the test method thereof is as follows:

[0082] Using the Sansi Zongheng powder compaction density tester, take 1-2g of negative electrode powder (first active silicon material, second active silicon material or active silicon material) into a mold with an inner hole diameter of 13mm, test pressure of 5t, hold pressure for 30s, and test the powder compaction density of the negative electrode material.

[0083] Examples & Comparative Examples

[0084] The present embodiment and comparative example respectively provide a negative electrode plate and a preparation method thereof, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, the components of the negative electrode active material layer comprising active silicon material, active carbon material conductive agent, binder and thickener; the active silicon material comprises a first active silicon material and a second active silicon material, and its specific material type, particle size, compaction density (compaction density PD1 of the first active silicon material, compaction density PD2 of the second active silicon material, compaction density PD of the active silicon material), content of the first active silicon material and the second active silicon material in the active silicon material, mass content of the active silicon material in the total mass of the active silicon material and the active carbon material, etc. are shown in Table 1.

[0085] The schematic diagram of the structure of the negative electrode sheet of Example 1 is as follows: Figure 1 As shown, the schematic diagram of particle crushing of the active silicon material on the surface of the negative electrode plate of Example 1 is as follows Figure 2 shown.

[0086] The preparation method comprises: mixing active silicon material, active carbon material, single-walled carbon nanotube, binder PAA and thickener, wherein the mass ratio of active silicon material to active carbon material is x%: (100-x)%, the mass sum of active silicon material and active carbon material, single-walled carbon nanotube, binder PAA and thickener CMC is 96.7%: 0.1%: 2.8%: 0.4%, adding appropriate amount of water, kneading at a solid content of about 60-75%. Adding appropriate amount of water, adjusting the viscosity of the slurry to 3000-8000 Pa·S, the solid content to 45-55%, and preparing negative electrode slurry. The prepared negative electrode slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet, wherein x% is the mass content of the active silicon material in the total mass of the active silicon material and the activated carbon material, as shown in Table 1.

[0087] Table 1

[0088]

[0089]

[0090]

[0091] Application Examples

[0092] The negative electrode sheets prepared in the examples and comparative examples are used to assemble lithium-ion batteries.

[0093] (1) Positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2 material is used as the positive electrode material. The positive electrode material, conductive carbon black, multi-walled carbon nanotubes and binder PVDF are mixed in a mass ratio of 97.5%:1.0%:0.5%:1.0%, and an appropriate amount of NMP is added to adjust the viscosity of the slurry to 3000-10000 Pa·S and the solid content of the slurry to 50-60% to prepare a positive electrode slurry. The prepared positive electrode slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet;

[0094] (2) Electrolyte: including organic solvent, lithium salt and additives; organic solvent: a mixed solvent of ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl methyl carbonate; lithium salt: lithium hexafluorophosphate and lithium difluorophosphate, with lithium hexafluorophosphate as the main salt and a concentration of 0.8-1.5 mol / L; additives: fluoroethylene carbonate, vinylene carbonate and vinyl sulfate;

[0095] (3) Diaphragm: polyethylene porous film;

[0096] (4) Assembly: The positive electrode, separator, and negative electrode are stacked in order, with the separator placed between the positive and negative electrodes to isolate them. The bare cells are placed in an outer package, and the electrolyte is injected and packaged. After the formation, degassing, and trimming processes, a lithium-ion battery is obtained.

[0097] It should be noted that the above-mentioned test lithium-ion battery is only an example listed for testing the performance of the negative electrode plate, and the present invention is not limited to this type of battery, wherein the raw materials (except the negative electrode plate), proportions, parameters and processes can be replaced with other conventional raw materials, proportions, parameters and processes in the art, thereby forming a battery different from the test lithium-ion battery.

[0098] Performance Testing

[0099] 1. Limit compaction density of negative electrode

[0100] Gradually adjust the pressure and roller gap of the roller press until the main body of the negative electrode plate becomes shiny and overpressure occurs. At this time, the plate is judged to be overpressured, and the plate thickness h1 is obtained. Combined with the plate coating surface density W and the substrate thickness h2, the ultimate compaction density is W / (h1-h2).

[0101] 2. The particle crushing ratio of active silicon material on the surface of negative electrode

[0102] Using a scanning electron microscope, under a 500X view, the total number of silicon particles A01 and the number of broken silicon particles A02 in the view were counted. A total of 10 views were counted, and the broken silicon particle ratio X = (A02+A12+A22+…+A82+A92) / (A01+A11+A21+…+A82+A91)×100%.

[0103] 3. Battery energy density

[0104] The energy density of the lithium-ion battery was measured by charging and discharging it at a constant current of 1C / 1C in the voltage range of 2.8V-4.25V.

[0105] 4. Battery 3C charging rate test:

[0106] At 25°C, discharge at 0.2C to 2.8V, let stand for 5 minutes, charge at 3C to 4.25V, charge at constant voltage to 0.05C and let stand for 5 minutes, the ratio of constant current charging capacity to total capacity is the charging rate.

[0107] 5. Battery lithium deposition and film stripping test:

[0108] After the lithium-ion battery is charged at 3C within the voltage range of 2.8-4.25V, the pole pieces are disassembled to observe the lithium deposition and film removal of the negative pole piece.

[0109] 6. Battery high temperature cycle performance test:

[0110] The test temperature is 45℃, charge to 4.25V at 1C constant current, charge to 0.025C at constant voltage, and discharge to 2.8V at 1C after standing for 5 minutes. Take the capacity obtained in this step as the initial capacity, perform 1C charge / 1C discharge cycle test, and compare the capacity of each step with the initial capacity to obtain the capacity decay curve. Record the capacity retention rate when cycling 500 times at 45℃ to compare the high temperature cycle performance of the battery.

[0111] 7. Electrode assembly full charge expansion rate test

[0112] The thickness of the fresh electrode assembly at half charge was tested with a spiral micrometer. When the electrode assembly was cycled to 500cls at 45°C, it was in a fully charged state. The thickness of the electrode assembly at this time was tested with a spiral micrometer again. By comparing it with the thickness of the fresh electrode assembly at the initial half charge, the expansion rate of the fully charged electrode assembly at this time could be obtained.

[0113] The test results are shown in Table 2:

[0114] Table 2

[0115]

[0116]

[0117] It can be found from Figure 1 and Table 2 that the negative electrode plate provided by the present invention has high strength and high compaction density, and the battery prepared using the negative electrode plate provided by the present invention has excellent kinetic performance and long cycle performance, and has a high energy density.

[0118] From the comparison between Examples 1-3 and Comparative Examples 1-2, it can be found that when the particle sizes of the first active silicon material and the second active silicon material are within the scope of the present invention, as the particle size of the second active silicon material increases, the compaction density of the active silicon material and the ultimate compaction density of the negative electrode plate both increase, the breakage ratio of silicon particles decreases, and the specific surface area of ​​the silicon material decreases, and the degree of side reactions of the electrolyte decreases, the cycle performance of the battery is improved, and the expansion is improved; when the particle size of the second active silicon material is too high (>10μm), the fast charging performance of the battery decreases, and even slight lithium precipitation occurs. This is because the excessive size of the silicon particles will lead to an increase in the transmission path of lithium ions inside the particles, thereby affecting its rate performance.

[0119] From the comparison of Examples 1, 4-5 and Comparative Examples 3-4, it can be found that when the particle size of the first active silicon material and the second active silicon material is within the scope of the present invention, as the particle size of the first active silicon material increases, the compaction density of the active silicon material and the ultimate compaction density of the negative electrode plate both increase, the silicon particle breakage ratio decreases, and the specific surface area of ​​the silicon material decreases, and the degree of side reactions with the electrolyte decreases, the cycle performance of the battery improves, and the expansion improves; when the particle size of the first active silicon material is too small (<1 μm), the compaction density is low, the particle grading effect is poor, and the compaction density of the active silicon material powder after grading is lower than that of the second active silicon material, resulting in a decrease in the compaction density of the electrode plate, a decrease in the battery energy density, and an increase in the crushing ratio of silicon particles, exposing more active silicon, and the specific surface area of ​​the first active silicon material increases, and the side reactions with the electrolyte intensify, resulting in deterioration of the rate performance, cycle performance and expansion performance. When the particle size of the first active silicon material is too large (>5 μm), the first active silicon material and the second active silicon material cannot form an effective particle grading, and the compaction density of the active silicon material is reduced. The increase in particle size leads to material kinetic loss and slight lithium precipitation.

[0120] From the comparison of Examples 1, 6-7 and Comparative Examples 7-8, it can be found that when the mass content of the first active silicon material in the active silicon material is 15-40%, a balance between the kinetic performance and the cyclic expansion performance can be achieved. As the content of the first active silicon material increases, the kinetic performance of the material is improved, but the increase in the first active silicon material with a smaller particle size leads to an increase in the total specific surface area, causing a slight deterioration in the cyclic performance and the expansion performance; but when the proportion of the first active silicon material is <15% or >40%, the content grading effect of the first active silicon material and the second active silicon material is poor, the compaction density of the active silicon material is lower than the compaction density of the second active silicon material, the energy density of the battery is reduced, and the proportion of broken silicon particles in the negative electrode sheet is increased, exposing more active silicon, and the specific surface area of ​​the first active silicon material is increased, and the side reactions of the electrolyte are intensified, resulting in a significant deterioration in the rate performance, cycle performance and expansion performance.

[0121] From the comparison of Examples 1, 8-11 and Comparative Examples 5-6, it can be found that when the mass content of the active silicon material in the negative electrode active material layer is 2-30%, especially in the range of 5-20%, the energy density of the battery can be effectively improved, and the cycle performance and expansion performance are both within an acceptable range. When the content of the active silicon material is less than 2%, the battery energy density is too low; when the proportion of the active silicon material is greater than 30%, the battery energy density is improved, but the kinetic performance, cycle performance and expansion performance are significantly deteriorated.

[0122] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0123] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the components of the negative electrode active material layer include active silicon material and active carbon material; The active silicon material comprises a first active silicon material and a second active silicon material. The Dv50 particle size of the first active silicon material is 1-5 μm, and the Dv50 particle size of the second active silicon material is 7-10 μm.

2. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the active silicon material being 100%, the mass content of the first active silicon material is 15-40%.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: Based on the total mass of the active silicon material and the active carbon material being 100%, the content of the active silicon material is 2-30%.

4. The negative electrode sheet according to claim 1 or 2, characterized in that: The particle breakage ratio of the active silicon material on the surface of the negative electrode plate is ≤5%.

5. The negative electrode sheet according to claim 1 or 2, characterized in that: The first active silicon material and the second active silicon material each independently include SiO x , any one or more of pre-lithiation silicon oxide, pre-magnesiation silicon oxide, silicon alloy, sand-ground silicon carbon and vapor-deposited silicon carbon, wherein 0<x<2; And / or, the activated carbon material includes any one or more of artificial graphite, natural graphite, soft carbon, hard carbon and mesophase carbon microbeads.

6. The negative electrode sheet according to claim 5, characterized in that: The compaction density PD1 of the first active silicon material is 0.95 g / cc≤PD1≤1.05 g / cc; and / or, the compaction density PD2 of the second active silicon material is 1.05 g / cc<PD2≤1.20 g / cc; And / or, the compaction density of the active silicon material PD>PD2.

7. The negative electrode sheet according to claim 1 or 2, characterized in that: The components of the negative electrode active material layer also include a conductive agent, a binder and a thickener.

8. The method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing active silicon material and active carbon material to obtain negative electrode active slurry, coating the negative electrode active slurry on the negative electrode current collector to obtain the negative electrode plate.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to any one of claims 1 to 7 or the negative electrode sheet prepared by the preparation method according to claim 8.

10. An electrical device, characterized in that: The electrical equipment comprises the lithium-ion battery according to claim 9.